Digital Media and Political Socialization: Implications for Nigeria's Democracy - Nwokeocha Ifeanyi Martins (CV. Rayyan Dwi Bharata, 2023)
Media are an important pillar of political socialization; that is the way a person learns about the functions of democratic principles and institutions in their formative years and beyond. Changes in the social and media environments affect the way citizens become politically socialized. With the emergence of digital media, communication has continued to change towards a socially networked, algorithmic and highly personalized environment. This new, networked communication logic, in which information is shared ubiquitously, accessible and aligned to personal interest, reshapes the mechanism through which media use can impact political socialization outcomes. While cultivation of universal perceptions in the population through mass media becomes less likely, political role models, previously found mostly in mass media can now be met in citizen's own online communities. This entry shed light on the interplay of digital media use and socialization outcomes and explains how a networked communication logic enhance good governance in Nigerian.